Maternal near miss: what lies beneath?. (April 2016) - O'Malley, Eimer G.; Popivanov, Petar; Fergus, Ann; Tan, Terry; Byrne, Bridgette
Abstract: Objective: Capturing 'near miss' and severe maternal morbidity using standard definitions is challenging. Information about levels of care required by ill pregnant or recently pregnant women may be more informative. The aim of this study was to prospectively audit incidence, causes, categorisation of maternal morbidity and level of care required by patients admitted to a labour ward high dependency unit (HDU) in a stand-alone obstetric hospital. Study design: All women admitted to HDU from May 5th to November 5th 2014 were identified prospectively and morbidity was categorised according to the Scottish Audit of Severe Maternal Morbidity (SAMM) and World Health Organisation (WHO) definitions of 'near miss' (NM), and 'severe maternal complications' (SMC). Level of care was determined by the RCOG Maternal critical care working group recommendations[1] . Results: There were 128 admissions to HDU with 4502 live births (2.8%) during this period. There were 16 (12.5%) cases of NM; 83 (64.8%) of SMC and 29 'others' not meeting either criteria. Direct obstetric causes accounted for 79% of admissions. NM cases were more likely to be caused by haemorrhage (56.3%, p  = 0.009), postpartum (75%, p  < 0.05) and require blood transfusion (56.4%) compared to SMC cases, more likely to result from hypertension (39.8%, p  = 0.018) and be admitted antenatally (66.3%, p  = 0.039). Those admitted in the beneath NM and SMC group were more likely to be admitted antenatally (89.7%, p  = 0.039) and require specialist consultation (31%, p  = 0.022). Mean duration of HDU stay was 26.6 (±17 SD) hours. The perinatal mortality rate was 39/1000 total births. There were no maternal deaths. Level 2 care was required by 40 women (NM 25%; SMC 39% and others 14%) and two women required ICU transfer for Level 3 care. Conclusions: Approximately one quarter of women requiring HDU care 'lie beneath' criteria for near miss or severe maternal complications. One third of women admitted to the HDU require Level 2 care and the remainder require higher levels of monitoring only. The majority of cases are antepartum and delivery is integral in their care. HDU care in a labour ward setting is a good model for care of the ill pregnant or recently pregnant woman.